Pengaruh Digital Marketing dan Kualitas Pelayanan terhadap Keputusan Pembelian di Online Shop Dujourexcloset - Situmorang, Debora H; Pasaribu, Veta Lidya Delimah (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to determine Digital Marketing (X1) Service Quality (X2), purchasing decisions (variable Y) so with the title (the influence of Digital Marketing and Service Quality on Purchasing Decisions at the Dujourexcloset Online Shop). The research method uses a quantitative approach which is associative with a population in this study of 9,533 in purchasing decisions. The sample used in this research was a sampling technique with the technique taken, namely purposive sampling and using the Slovin formula, which is a formula used to find a sample size that is considered capable of representing the entire population and using a Maximum Margin of Error of 0.10 or 10% so that it can be obtained. The sample was 99 respondents. The partial digital marketing test results have a significant effect on purchasing decisions with a calculated t value > t table or (7,699 > 1.661). This is also reinforced by the ρ value < Sig.0.05 or (0.000 < 0.05). The results of service quality partially have a significant effect on purchasing decisions with the calculated t value > t table or (6,684 > 1.661). This is also reinforced by the ρ value < Sig.0.05 or (0.000 < 0.05). Digital marketing results and service quality simultaneously influence purchasing decisions with a calculated F value > F table or (15,498 > 3.09), this is also reinforced by a ρ value < Sig.0.05 or (0.000 < 0.05). Keywords: Digital Marketing, Purchasing Decisions, Service Quality.